Designing PrEP and early HIV treatment interventions for implementation among female sex workers in South Africa: developing and learning from a formative research process. Issue 6 (14th June 2018) - Eakle, Robyn; Mutanha, Nyaradzo; Mbogua, Judie; Sibanyoni, Maria; Bourne, Adam; Gomez, Gabriela; Venter, Francois; Rees, Helen
Abstract : Objectives: The objective of this research was to design relevant, tailored oral pre-exposure prophylaxis (PrEP) and early antiretroviral (ART) interventions for female sex workers (FSWs) in South Africa. This paper examines the methods, process and outcomes of employing an inductive approach to formative research exploring intervention feasibility and acceptability. Setting: Research was conducted in several sex work-related settings including five sites in and around clinics and stakeholder offices. Participants: Participants in this research included stakeholders, experts in the field and FSWs. This included at least 25 separate engagements, 14 local organisations and 8 focus group discussions (FGDs) with 69 participants, in addition to ad hoc meetings. Results: The first set of outcomes consisted of five selected methods: (1) stakeholder consultations; (2) site assessments and selection; (3) field observations and mapping; (4) development of supportive structures to encourage retention and intervention adherence; (5) FGDs conducted with FSWs to explore specifics of acceptability. In terms of feasibility, two sites were selected in central Johannesburg and Pretoria out of five considered. The urban site contexts varied, necessitating adjustments to intervention implementation. There was overall support for PrEP and early ART from stakeholders and FSWs. Concerns included potential issues with adherence to PrEP (and early ART), possible reduction in condom use, resistance to antiretrovirals and burden on scarce resources. These concerns indicated where special attention should be focused on education, messaging and programming as well as development of supportive structures. Conclusions: The inductive approach allowed for a wide range of perspectives, defining population needs and accessibility. This research illustrated how similar sex work environments can vary and how implementation of interventions may not be uniform across contexts. Lessons learnt in details could assist in future project designs and implementation of new interventions where feasibility, social and cultural factors affecting acceptability must be considered.